(untitled) (Journal of Applied Learning and Teaching, 2025)
Management education faces challenges. Expectations from various stakeholders, governments, employers and learners have compelled higher education institutions to reimagine students’ learning experiences and address the skills gap in the job market. One major challenge is course design and delivery. Education needs to be both relevant and practical as students are one step away from entering the workforce. Therefore, incorporating experiential learning into the curriculum is highly desirable. Experiential learning pedagogy is growing in popularity in higher education as it provides students with invaluable experience working on real business cases. It also prepares them for their professional endeavours ahead. This paper shows an industry collaborative project of University College Dublin (UCD) in Singapore. The project required students to collect firsthand data and apply their knowledge and skills to building a sustainable three-sided marketplace of online food delivery service. The four components of Kolb’s learning cycle – concrete experience, reflection observation, abstract conceptualisation, and active experimentation – have been shown to transform students’ learning experiences and achieve a variety of learning outcomes. This paper also documents the project goals, work progress, obstacles encountered, and reflections.